Calcium action potentials in hair cells pattern auditory neuron activity before hearing onset - Tritsch, Nicolas X. (2010)
We found that rat central auditory neurons fire action potentials in a precise sequence of mini-bursts prior to hearing onset. This stereotyped pattern is initiated by hair cells within the cochlea, which trigger brief bursts of action potentials in auditory neurons each time they fire a Ca(2+) spike. By generating theta-like activity, hair cells may limit the influence of synaptic depression in developing auditory circuits and promote consolidation of synapses.